Teks Bulan Mekalangan Karya I Nyoman Manda; Analisis Struktur dan Nilai - Ayu Dendriani, I Gusti; Duana Sutika, I Nyoman; Sutama, Putu (Humanis; Volume 17. No. 1. Oktober 2016, 2016)
This study examines modern Balinese literary works in the form of narrative text. Text studied is the Bulan Mekalangan works of I Nyoman Manda. Text tells about the love story of Raden Inu Kertapati with Diah Candra Kirana that originated from matchmaking. This study uses a structural theory of Teeuw, Marsono and Nurgiyantoro. Methods and techniques in this study were divided into three stages, namely stage data provision by using the method of literature study and reading method supported by tercemahan and recording techniques. Data analysis stage using methods of qualitative and descriptive analytic techniques. The last stage is the stage of presentation of the results of data analysis using informal methods and supported by deductive and inductive techniques. The results obtained in this study is the structure and value of the Moon Mekalangan text. Structural features include the structure forma Mekalangan Bulan consisting of a variety of language and style. Based on the variety of language textce languages ?? Mekalangan Bali Bali Alus include alkaline, alkaline andap Bali, Bali bases rude. Style of language used is the language style comparisons and contradictions. Bulan Mekalangan textce narrative structure consists of incident, plot, (straight groove), background (background of the place, time and atmosphere), character and characterization, viewpoints and themes. The value analysis conducted in text Bulan Mekalangan is a religious value which includes tattwa (philosophy), ethical (moral), and the ceremony (ritual), the value of loyalty, the value of education, leadership values ??and historical values